A cross sectional study on knowledge, attitude and practice regarding spacing methods among married women of the reproductive age group in the field practice area of UHTC in surendranagar district - Shyamal K. Purani; Girija Kartha; Darshan K. Mahyavanshi; Mitali G. Patel; Sunita S. Nagar (Indian Association of Preventive and Social Medicine, 2011)
India was the first country in the world to launch a National Family Planning Programme with aim to reduce the birth rate to stabilize population. To improve effectiveness of programme, various segments of our population need to have the apt awareness regarding the various spacing methods. This study is aimed at finding out the awareness among the women of the same